An intercept study to measure the extent to which New Zealand university students pre‐game - Benjamin C. Riordan; Tamlin S. Conner; Jayde A. M. Flett; Nic Droste; Louise Cody; Kate L. Brookie; Jessica K. Riordan; Damian Scarf (Elsevier, 2018)
Abstract Objective: We aimed to quantify the degree to which students pre‐gamed in New Zealand, using self‐report and breathalysers. Methods: A total of 569 New Zealand undergraduate students were interviewed (men = 45.2%; first year = 81.4%) entering three university‐run concerts. We asked participants to report how many drinks they had consumed, their self‐reported intoxication and the duration of their pre‐gaming session. We then recorded participants' Breath Alcohol Concentration (BrAC; µg/L) and the time they arrived at the event. Results: The number of participants who reported consuming alcohol before the event was 504 (88.6%) and the number of standard drinks consumed was high (M=6.9; median=6.0). A total of 237 (41.7%) participants could not have their BrAC recorded due to having consumed alcohol ≤10 minutes before the interview. The remaining 332 participants (57.3%) recorded a mean BrAC of 288.8µg/L (median=280.0 µg/L). Gender, off‐campus accommodation, length of pre‐gaming drinking session, and time of arrival at the event were all associated with increased pre‐gaming. Conclusion and implications for public health: Pre‐gaming was the norm for students. Universities must take pre‐gaming into account; policy implications include earlier start times of events and limiting students' access to alcohol prior to events.